2-Acetamido-N-benzyl-1,4-imino-1,2,4-tride-oxy-l-xylitol (N-benzyl-l-XYLNAc). - Jenkinson, S; Crabtree, E; Glawar, A; Butters, T; Fleet, G; Watkin, D (2010)
X-ray crystallography defines the relative configuration at the three-stereogenic centres in the title compound N-benzyl-l-XYLNAc, C(14)H(20)N(2)O(3). The five-membered pyrrolidine ring adopts an envelope conformation with the N atom lying out of the plane of the other four atoms. In the crystal structure, inter-molecular O-H⋯O, N-H⋯O and O-H⋯N hydrogen bonds link the mol-ecules into chains along [100]. The carbonyl group O atom acts as an acceptor for a bifurcated hydrogen bond. The absolute configuration is determined by the use of l-glucuronolactone as the starting material for the synthesis.